Tourette syndrome: Review of literature - Teixeira, Larissa Lane Cardoso; Pantoja, José Mariano Soriano, Júnior; Neto, Francisco Xavier Palheta; Targino, Mauricio Neres; Palheta, Angélica Cristina Pezzin; da Silva, Felipe Araújo (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Tourette Syndrome (TS) was described for the first time in 1825, and it is a neuropsychiatry disease, initially begins in childhood, affects more males, characterized by remarkable social and psychological commitment, impacting the lives of patients and family. Until recently, this disease were considered a rare condition, but current studies show that the prevalence rate may vary in 1% to 2,9% in a few groups.Objective: Perform a review of literature over the main aspects related to Tourette syndrome.Data synthesis: The TS is a genetic disorder, associated with neuroanatomical and neurophysiological alterations, characterized by compulsive phenomenon, whose etiology is still unknown. The clinical profile is composed, mostly, by motor tics and vocal tics, that which are divided in simple and complex. Its association with Obssessive Compulsive Disorder and Attention Deficit Hyperactivity Disorder is very commom. The diagnosis is mainly clinical and do not exist. Until now, there is no specific laboratory test that confirm this pathology. The treatment is based mainly on psychological theory. However when there is need for the use of drugs, the most widely used are the antagonists of dopamine receptors.Conclusion: The TS causes many damages as psychosocial and educational for the individual and the family. However, the diagnosis and the early treatment are able to minimize or cancel this damages. This way, knowing the general aspects that guide the TS is of utmost importance to preserve the quality of life for the patients with the disease.
Keywords: Tourette syndrome; tics; otorhinolaryngologic diseases; voice disorders